EXTENSIONS OF PHYSICAL EDUCATION AND SPORT INTO THE PERFORMING ARTS - Luminița MILEA (Cluj University Press, 2017)
Extensions of Physical Education and Sport into the Performing Arts. For the acting student, physical education and sport have formative valences, developing influence relationships into the study of stage movement and body expressiveness. The actor's physical training or the creative art behind a successful role engage all the components of the human being, combining the body's physical education with mental education, in complete harmony. For obtaining the acting performance, the established methods and techniques of the major theater schools of the 20th century that underlie the actor's professional training are enriched with new formulas and currents specific to the actor's art, physical education and sport. With an interdisciplinary approach, physical education and sport, through specific means, naturally intersect with the other formative components focused on the actor, on his physical form, on the ability to understand and artistic expression. By influencing each other, these methods hone the actor's path to professional fulfillment and assume his living presence in a scenic space at a given time. In the equation of the actor's training, based on their professional experience and knowledge, all trainers will be involved alongside, instituting methods of progressive training appropriate to contemporary times. REZUMAT. Extensii ale educației fizice și sportului în artele spectacolului. Pentru studentul la actorie, educația fizică și sportul au valențe formative, dezvoltând relații de influență în studiul mișcării scenice și a expresivității corporale. Antrenamentul fizic al actorului sau munca de creație cu succes a unui rol angrenează toate componentele ființei umane, combinând educația fizică a corpului cu educația psihică, într-o deplină armonie. Pentru obținerea performanței actoricești, metodele și tehnicile consacrate ale marilor școli de teatru de secol XX ce stau la baza formării profesionale a actorului, sunt îmbogățite cu formule și curente noi specifice artei actorului, educației fizice și sportului. Printr-o abordare interdisciplinară, educația fizică și sportul, prin mijloacele specifice se intersectează în mod firesc cu celelalte componente formative focusate pe actor, pe forma sa fizică, pe capacitatea de înțelegere și exprimare artistică. Influențându-se reciproc, aceste metode jalonează calea actorului spre desavârșirea profesională și asumarea prezenței sale vii într-un spațiu scenic și un moment dat. În ecuația formării actorului, bazându-se pe experiența și cunoștințele profesionale, se vor implica cot la cot toți formatorii, instituind metode de antrenare în progres, adecvate contemporaneității. Cuvinte cheie: antrenament fizic, formativ, mișcare scenică, expresivitate corporală, corp, voce.